X-Men. First class - Vaughn, Matthew, 1971-; Shuler-Donner, Lauren; McAvoy, James, 1979-; Fassbender, Michael, 1977-; Bacon, Kevin, 1958-; Byrne, Rose.; Jones, January, 1978-; Platt, Oliver; Marvel Entertainment Group; Bad Hat Harry Productions; Donner's Company (Firm); Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2011)
Tells the story of the origins of the X-Men as Charles Xavier and Erik Lehnsherr discover their powers, join forces to work for Division X, and seek out other mutants to prevent a global nuclear war.
Special features: "Children of the atom: Second genesis and Band of brothers", featurette.
Originally released as a motion picture in 2011.
Director of photography, John Mathieson ; editors, Lee Smith, Eddie Hamilton ; music, Henry Jackman.
James McAvoy, Michael Fassbender, Kevin Bacon, Rose Byrne, January Jones, Oliver Platt.
MPAA rating: PG-13; for intense sequences of action and violence, some sexual content including brief partial nudity and language.
DVD ; widescreen (2.35:1) presentation ; Dolby digital 5.1 surround.
Keywords: X-Men (Fictitious characters) -- Drama; Mutation (Biology) -- Drama; Nuclear warfare -- Drama; Science fiction films; Action and adventure films; Films for the hearing impaired; Feature films